Analisis Pengolahan Biji Salak Menjadi Bubuk Kopi dari Limbah Toko Bolu Salak di Kota Padang Sidimpuan: Penelitian - Silvia Annur Hasibuan; Amelia; Monika Flora Manik; Rini Khairani Harahap; Rejosu Vanhot Sianturi; Putri Kemala Dewi Lubis (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to utilize salak seed waste from Bolu Salak (a fruit cake shop) in Padangsidimpuan City as a raw material for making coffee powder, which has economic value and market potential. Unmanaged salak seed waste poses a risk of environmental pollution, necessitating creative processing that can provide added value. The study used an experimental method supplemented by literature review and interviews. The processing process included cleaning, drying, roasting, grinding, and filtering to produce coffee powder with a distinctive aroma and a consumable texture. The results showed that salak seeds contain antioxidants and are low in caffeine, making them a potential healthier beverage alternative. Product innovation was carried out through a ready-to-brew formulation, the use of sachet packaging, and the development of a ready-to-drink bottle variant. Public and student responses to the product's taste, aroma, and uniqueness demonstrated positive acceptance. This study concludes that processing salak seeds into coffee powder is an effective way to reduce organic waste while opening up business opportunities based on local wisdom in Padangsidimpuan City.